EKSPLORASI WARNA QUEEN ANGELFISH PADA BUSANA PESTA SORE - Siti Muthi Aulia; Astuti Astuti (Universitas Pendidikan Indonesia, 2017)
The development of the creativity of a designer in the work is absolutely required to produce works that differ from existing. The diversity of sources of ideas are challenges that need to be solved with the creativity of designers to produce a unique and interesting work. Queen Angelfish are fish coral reef dwellers that have beautiful colors so that the author is interested in making the fish as a source of ideas on the creation of products of this report. The colors are owned by the Queen Angelfish include blue, dark blue, yellow and aqua. The author colors to apply to the making of an afternoon party dress by using application engineering cut motifs and broomstick pleats as one motif to bring up the color through the motifs resembling scales, crown and stilasi form of tail fins and Queen Angelfish. Party dress evening dress sense has been used on the occasion of the party in the afternoon between the hours of 3 p.m. to 6 p.m. as a celebratory event. The use of the color Queen Angelfish on this occasion can make the wearer as the center of attention of people around, so the wearer appear confident in the presence of invited guests. Based on the explanation the authors tried to pour his creativity through report writing and making products that are titled